2011
DOI: 10.21608/jssae.2011.55445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic and Inorganic Fertilizers on Soil Nutrients Availability and Wheat Productivity.

Abstract: Soils degraded physically and nutritionally due to continuous use of chemical fertilizers under intensive agricultural. Management of N is the key for sustainable and profitable wheat production in a low N-soil availability. So a field experiment was conducted on a clay soil using wheat (Triticum aestivum) Giza 168 variety during 2008 / 2009 season at Agricultural Experimental Station of Fac. Agric, Mansoura Univ., to study the influence of combined use of mineral fertilizers (urea) and organic fertilizers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…This is might attributed to the integrated use of inorganic fertilizers with organic manure sustains higher crop yield, maintain soil health and gave the optimum availability of NH 4 + , NO 3 -, P, K availability microelements . These results are confirmed with those obtained by Hammad et al, (2006) , Hammad et al (2011) and Naeem (2006…”
Section: Organic Manure Bio-treating × Mineral Fertilization Effectssupporting
confidence: 93%
“…This is might attributed to the integrated use of inorganic fertilizers with organic manure sustains higher crop yield, maintain soil health and gave the optimum availability of NH 4 + , NO 3 -, P, K availability microelements . These results are confirmed with those obtained by Hammad et al, (2006) , Hammad et al (2011) and Naeem (2006…”
Section: Organic Manure Bio-treating × Mineral Fertilization Effectssupporting
confidence: 93%
“…of branches and umbels plant -1 (90.64 cm, 6.52 branches and 24.62 umbels) were recorded in the first season by using FYM at the rate of 30m 3 fad -1 . The superiority of plant treated with ( CP) is may be due to its high contains organic matter and nutrients than (FYM) according to our analyses before planting (Table 2)and this finding are in agreement with Hammad et al(2011) who reported that compost is considered an excellent source of organic matter and addition of compost will increase soil organic matter levels more quickly than another manures and slurries .Also these results are in harmony with the finding of Abdou et al,(2015) who revealed that vegetative growth characters of coriander plant were significantly increased due to the application of all levels of compost. NPK, Bio-Fertilizer and Foliar applications effect.…”
Section: Organic Fertilization Effectsupporting
confidence: 90%
“…1-.These findings are in agreement with those obtained by Singh and Agrawal, (2005) who reported that application of 10 and 20 tones ha -1 FYM increased the grains yield and the total N P and K uptake in wheat crop. Also, Hammad et al (2011) found a positive effect of organic fertilizers on soil nutrients availability and wheat productivity.…”
Section: Resultsmentioning
confidence: 94%